Ionic liquid-hydroxide-mediated low-temperature synthesis of high-entropy perovskite oxide nanoparticles. Issue 21 (9th March 2022) - Shi, Yingying; Xu, Qiuchen; Tian, Zhangmin; Liu, Guiying; Ma, Chenxu; Zheng, Wenjun
Abstract : In this paper, a novel synthetic strategy for high-entropy perovskite oxide nanoparticles is reported using an ionic liquid-hydroxide-mediated technique at a low temperature (200 °C or lower) and normal atmospheric pressure. Abstract : High-entropy perovskite oxides (HEPOs) are attracting significant attention due to their unique structures, unprecedented properties and great application potential in many fields, while available synthetic methods have many shortcomings; so it is still a challenge to develop a simple, low-cost and environment-friendly synthetic strategy for HEPOs. Herein, a novel synthetic strategy is reported for HEPOs using an ionic liquid (IL)-hydroxide-mediated technique at a low temperature and normal atmospheric pressure. The synthesized HEPOs, including Ba(FeNbTiZrTa)O3, Ba(MnNbTiZrTa)O3, Ba(FeSnTiZrTa)O3 and Ba(FeVTiZrTa)O3, exhibit a cubic structure and a dispersed nanoparticle morphology (particle size of 20–60 nm). The formation process of HEPOs in an IL-KOH system can be described as follows: first, B-site metal source compounds are dissolved in IL-KOH medium to form hydroxyl complexes; second, the complexes further dehydrate, condensate and react with Ba 2+ ions to form the crystal nuclei of HEPOs under the synergistic effect of reaction temperature and basicity; third, the growth of HEPO nuclei is completed by the Ostwald ripening process. In these processes, KOH not only plays a role as a solvent, but also provides sufficient OH − concentration for the formation and condensation of B-site metal hydroxyl complexes, while the IL also makes significant contributions: first, a lower reaction temperature and lower dosage of KOH are achieved by the use of the IL; second, the IL with good dissolving ability and low surface tensions can promote the nucleation rate of HEPOs and improve the Ostwald ripening process; third, the compact adsorption of the IL on the surface of products ensures a small particle size and high dispersion of HEPO nanoparticles to a certain extent. In brief, the technique provides an innovative, low-cost, simple and nontoxic strategy for the synthesis of HEPOs, which can be extended to other high-entropy materials.